2018
DOI: 10.1136/bmjsrh-2018-200102
|View full text |Cite
|
Sign up to set email alerts
|

Second-trimester medication abortion outside the clinic setting: an analysis of electronic client records from a safe abortion hotline in Indonesia

Abstract: IntroductionUnsafe abortion past the first trimester disproportionately accounts for the majority of global abortion-related morbidity and mortality; research that documents the safety, feasibility and acceptability of existing models for providing information and support to women who self-manage outside of formal clinic settings is needed.MethodsThis study is a retrospective analysis of anonymised electronic client records from callers to a safe abortion hotline in Indonesia. Between July 2012 and October 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 23 publications
6
52
0
Order By: Relevance
“…(6)(7)(8)(9)(10) There is a growing body of literature from around the world indicating that when individuals have access to information about how to obtain the pills, how to take the pills, how to assess for completion, and warning signs that may indicate potential complications, the practice of selfmanaged medication abortion is safe and the experience satisfactory. (8,9,(11)(12)(13)(14)(15) Much of the published literature has focused speci cally on the experiences of self-managed medication abortion with telemedicine support from online websites that provide access to pills as well as information on how to use them via email communication; these studies report safe and effective abortion experiences. (2,8,12,13,(16)(17)(18) Beyond online websites, people obtain information, medications, and support to self-manage their abortions in a variety of other ways as well.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…(6)(7)(8)(9)(10) There is a growing body of literature from around the world indicating that when individuals have access to information about how to obtain the pills, how to take the pills, how to assess for completion, and warning signs that may indicate potential complications, the practice of selfmanaged medication abortion is safe and the experience satisfactory. (8,9,(11)(12)(13)(14)(15) Much of the published literature has focused speci cally on the experiences of self-managed medication abortion with telemedicine support from online websites that provide access to pills as well as information on how to use them via email communication; these studies report safe and effective abortion experiences. (2,8,12,13,(16)(17)(18) Beyond online websites, people obtain information, medications, and support to self-manage their abortions in a variety of other ways as well.…”
Section: Introductionmentioning
confidence: 99%
“…One emerging model is abortion accompaniment, where trained volunteers provide WHO-recommended evidence-based information about medication abortion, as well as physical and emotional support and person-centered care throughout the medication abortion process, over the phone or in person, outside of the formal health care system. (15,(19)(20)(21)(22) This non-clinic based model of counselor-supported self-managed medication abortion care has come to be known as the "accompaniment model," as people are virtually "accompanied" through the medication abortion process. Approximately fty accompaniment groups are in operation around the world, providing support and information about self-managed medication abortion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For decades, people around the world have relied on WHO‐recommended medications to terminate unwanted pregnancies, increasingly in contexts where formal‐sector abortion care is restricted, expensive, and/or inaccessible . Studies have suggested that when individuals have accurate information about medication abortion protocols and about what to expect, access to quality medications, and access to follow‐up care if needed, they can safely and effectively manage their own abortions …”
Section: Introductionmentioning
confidence: 99%